Thinking Prevents Grave Evil: An Analysis of Thinking According to Hannah Arendt - Shelomita Selamat; Yustinus Yustinus (International Journal of Indonesian Philosophy & Theology, 2022)
Hannah Arendt identifies that, in most cases, human evil is banal. People who committed grave evil did not think profoundly about what they were doing, and it did not come from what we consider their “optio Fundamentalis”. This study endeavours to critically explore Hannah Arendt’s account of “Thinking” as a fundamental capacity of human existence. This study aims to investigate Hannah Arendt’s thoughts on Thinking and its relation to other human capacities and actions. We will utilize a critical analysis of Arendt’s works as the method of this study. We will critically analyze her important works, such as Eichmann in Jerusalem: A Report on the Banality of Evil, The Life of the Mind, and Essays in Understanding: 1930-1954, while her other works will also be considered. After this study, we find that the activity of Thinking is an essential capacity of the human being as a moral being. Only if human beings think profoundly, he/she can they produce meaningful actions that can hinder them from banal actions, which could even lead them to commit grave evils. The moral capacity of human beings remains in their act of Thinking. The need for exercising the activity of profound Thinking is, therefore, implied.